Handbook of special librarianship and information work - Ashworth, Wilfred (London : Aslib, 1967)
This book covers special library ,administration, acquisition , Cataloguing and indexing and classification.
Includes Index.
aia 05/07/2017
Loans
Keywords: Library science; Special libraries -- Great Britain -- Handbooks, manuals, etc; Information services -- Great Britain -- Handbooks, manuals, etc; Library science -- Great Britain -- Handbooks, manuals, etc; Special libraries; Information services; Special libraries